MAKNA TRADISI TABUIK OLEH MASYARAKAT KOTA PARIAMAN (STUDI DESKRIPTIF INTERAKSIONISME SIMBOLIK) - M.A Dalmeda; Novi Elian (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2016)
Tabuik Tradition is one of the activities conducted annually in Pariaman City. Rooted in religious values to commemorate the death of the Prophet Muhammad's grandson, Hussein. This anniversary actually takes place every 10th of Muharram Hijriyah calendar. This research uses case study observation design. Through observation techniques in the case study can be obtained detailed information or empirical information and accurate from the unit of research analysis. Tabuik ceremony represents a reflection of attitude and lifestyle of Pariaman society. Tabuik even made a tradition for the community that can not be separated from the lives of citizens Pariaman. Then, Tabuik implemented by Anak Nagari in the form of Tabuik Culture of Tabuik Meaning formed by each side. By society, tabuik serve as a venue for entertainment. By the government, tabuik serve as the agenda of tourism, while by urang tabuik, tabuik still used as a cultural tradition that should be preserved. The process of desacralization occurs due to the challenge of the taboo age developed in accordance with the ideology. The implementation of the tabuik has shifted considerably, but it is still maintained as a cultural tradition of the Pariaman community.